2014
DOI: 10.1080/02673037.2014.973386
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Local Context and Cultural Background: Somalis' Perceived Possibilities in Nordic Capitals' Housing Markets

Abstract: Immigrants' housing position is often explained by (lack of) resources or differences in cultural backgrounds. Recent studies have included the importance of local context. The aim of this paper is to examine Somalis' perceptions of their possibilities in four Nordic capitals' housing markets: Copenhagen, Helsinki, Oslo and Stockholm. The approach is an interview study based on immigrants' own explanations of what they strive for and how they assess the impact of local conditions and cultural background for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 34 publications
(54 reference statements)
0
12
0
1
Order By: Relevance
“…The descriptive analysis also revealed that, compared with natives, migrants both have a lower propensity to leave distressed areas and take a longer time to do so. Practices of ethnic discrimination in the Swedish housing market have been documented by existing qualitative research (e.g., Molina, ; Skovgaard Nielsen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive analysis also revealed that, compared with natives, migrants both have a lower propensity to leave distressed areas and take a longer time to do so. Practices of ethnic discrimination in the Swedish housing market have been documented by existing qualitative research (e.g., Molina, ; Skovgaard Nielsen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests several actors that can potentially discriminate against minority groups, namely, bankers, mortgage lending institutions, estate agents, and rental housing administrators. Private rental housing companies may, for instance, include special restrictions, aiming at excluding more disadvantaged groups (Andersson, Bråmå, & Hogdal, ; Skovgaard Nielsen, Holmqvist, Dhalmann, & Soholt, ). Recent research also argues that the lack of certain cognitive resources may undermine migrants' position in the housing market.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Thus, Turks and Poles are finding their way into the mainstream tenure structure. The low share of Somali homeowners can be explained by low purchasing power, religion-based reluctance to take up mortgages, and uncertainties about return to Somalia (Søholt 2013;Nielsen et al 2015). People of Turkish, Somali and Polish backgrounds have developed different residential patterns in Oslo.…”
Section: The Turkish Somali and Polish Populations In Oslomentioning
confidence: 99%
“…I sometimes refer to them as ' ethnic Somalis', defining ethnicity through the mother tongue. Substantial research has been conducted on, with, and by Finnish Somalis concerning their participation in civil society (Tiilikainen & Mohamed 2013), civic integration (Harinen et al 2013), battles for citizenship (Sotkasiira & Haverinen 2016), perceived possibilities and residential preferences (Dhalmann 2013;Nielsen, Holmqvist & Dhalmann 2015). However, their leisure patterns and the power relations at play in them remain largely unexplored.…”
Section: Finnish Somalismentioning
confidence: 99%